TENUN SONGKET PANDAI SIKEK DALAM BUDAYA MASYARAKAT MINANGKABAU - Yandri, Yandri (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2014)
The art of songket woven handicraft Pandai Sikek is a cultural product of collective creation and traditional heritage Pandai Sikek. Songket first created to meet human needs for traditional ceremonies such as wedding ceremony of Minangkabau. The symbolic meanings in the art of songket are constantly evolving in accordance with the change of time. The art of songket weave Pandai Sikek is one of the traditional handicrafts, which is used for wedding ceremony. In traditional wedding, the groom wears songket for ‘saluak’, ‘sisampiang’, and ‘cawek’, all of them accessories for the traditional costume, while the bride wears gloves, scarves, and tingkuluak, accessories for female constume. The use of songket is customary responsibility and each of the songket patterns contains symbolic meanings. Various decorative patterns of Minangkabau songket are inspired from the concept of